Screening of seaweed for antioxidant activity - Mamood, Mariah (2013)
The distribution and life form of seaweed in Merambong shoal was recorded. Based on the growth forms, epipelic seaweed particularly from Rhodophyta division was the most abundant life form with values of 89.66% and the lowest was epilithic with values of 13.79%. On the other hand, the antioxidant activity of 13 Malaysian seaweeds around different location in Peninsular Malaysia was also evaluated. The antioxidant activities were determined by two assays, TEAC (trolox equivalent antioxidant capacity) and DPPH (2, 2-diphenyl-1-pricrylhydrazyl) assays. In this study, the highest antioxidant activity was from the methanolic extracts of brown seaweed in DPPH assay e.g., Sargassum cristaefolium with values of more than 45% while the green seaweed showed low antioxidant activity with values less than 15%. Meanwhile, for TEAC assay no significant differences were observed between all the seaweed samples from different location. The highest antioxidant activity was from Halimeda macroloba with values of 0.53±0.18 mM.mg-1 dry extract. In conclusion, the studies showed that seaweeds have the potential as source of natural antioxidant.